1999
DOI: 10.1152/jappl.1999.86.1.418
|View full text |Cite
|
Sign up to set email alerts
|

Estimating respiratory mechanics in the presence of flow limitation

Abstract: Dynamic collapse of the pulmonary airways, leading to flow limitation, is a significant event in a number of respiratory pathologies, including obstructive sleep apnea syndrome and chronic obstructive pulmonary disease. Quantitative evaluation of the mechanical status of the respiratory system in these conditions provides useful insights into airway caliber and tissue stiffness, which are hallmarks of such abnormalities. However, assessing respiratory mechanics in the presence of flow limitation is problematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…These findings suggest, therefore, that the failure of RS to prevent pharyngeal narrowing and improve flow limitation in patients with OSA may be due to a relatively low RS (17) and/or arousal before all dilator muscles involved in pharyngeal stabilization were recruited (40). Furthermore, structural characteristics of the pharynx of OSA patients and mechanical phenomena associated with airflow may be relevant (1,24,29). It is also worth noting that RS had no effect on the endexpiratory CSA of the pharynx, whereas HG-ES enlarged the pharynx similarly during expiration and inspiration.…”
Section: Discussionmentioning
confidence: 91%
“…These findings suggest, therefore, that the failure of RS to prevent pharyngeal narrowing and improve flow limitation in patients with OSA may be due to a relatively low RS (17) and/or arousal before all dilator muscles involved in pharyngeal stabilization were recruited (40). Furthermore, structural characteristics of the pharynx of OSA patients and mechanical phenomena associated with airflow may be relevant (1,24,29). It is also worth noting that RS had no effect on the endexpiratory CSA of the pharynx, whereas HG-ES enlarged the pharynx similarly during expiration and inspiration.…”
Section: Discussionmentioning
confidence: 91%
“…Ayappa and co‐workers [2] demonstrated that flow limitation occurred more often than snoring (either preceding snoring or occurring simultaneously with snoring) during continuous positive airway pressure titration. Previously published results on bilevel PAP ventilation in sleep apnoea patients have shown that flow‐limited breaths reappear during therapy and that these effects may worsen with higher differences between inspiratory and expiratory pressures [3]. These studies also suggest that inspiratory flow limitation can occur with decreasing expiratory pressure even if the inspiratory pressure level is set at an effective level.…”
Section: Discussionmentioning
confidence: 91%
“…Oesophageal pressure fluctuations have been widely used as a marker [5, 7, 12, 16], but no defined cut‐off level exists for this criterion. Respiratory resistance has also been used as a criterion for flow limitation in other studies, but several different definitions of respiratory resistance have been employed [3, 9, 15, 18]. Faced with these problems, we decided to use two different definitions of flow limitation (oesophageal pressure and respiratory resistance defined as ΔP es / peakinsp , with a statistical criterion for defining the classification of the measured signals: 2 standard deviations above the mean level determined during quiet waking respiration).…”
Section: Discussionmentioning
confidence: 99%
“…This leads yet to another new feature of the model. While in previous models the lung volume remained constant during the study, here the inspiratory and expiratory phases are explicitly modelled by a linear algebraic equation (AE) relating the respiratory pump muscle effort and the lung volume in a similar fashion to models of respiratory mechanics during spontaneous quiet breathing (Lorino et al, 1982) and lower airway flow limitation (Bijaoui et al, 1999). This type of model lung has been applied in testing (Mecklenburgh et al, 1992), monitoring (Baconnier et al, 1995), and analysing (Crooke et al, 1998) the performance of mechanical ventilators.…”
Section: Theoretical Modelsmentioning
confidence: 99%